A study on the anti-hyperglycemic potential of bran extracts of coconut, rice and selected beans - Abd Aziz, Nuurhaffiszzul'llah (2015)
The diabetic patient is increasing year by year. The need in reducing the diabetic patient is not easy even though there are many ways in diabetes management. This is partly due to the side effect of the using drugs in controlling blood glucose level. The side effect may reduce by consuming organic products. Anti-hyperglycemic and antioxidant properties of bran extracts of coconut (Cocos nucifera), some selected beans (Phaseolus vulgaris) and rice (Oryza sativa) were investigated. Result showed that rice bran extracts was the most potential organic product that can be used to inhibit the α-amylase activity (96.180%). Meanwhile, red bean bran extract were the most potential to inhibit α-glucosidase activity (39.567%). Red bean bran extract contain the highest phenolic content (0.122 mg/g), while red kidney bean bran extract was potential organic product that can be used as antioxidant power (75.943 μg/ml). Meanwhile for ABTS and DPPH free radical scavenging, different dose of concentration were studied. The highest potential in ABTS free radical for scavenging 50 μg/ml of bran extract is rice bran extract (39.027 μmol/g), for 100 μg/ml of bran extract is white bean bran extract (47.050 μmol/g) and for 200 μg/ml of bran extract is coconut bran extract (49.850 μmol/g). Meanwhile, the highest potential in scavenging free radical DPPH for 50 μg/ml of bran extract is coconut bran extract (91.197 μmol/g) and for 100 and 200 μg/ml of bran extract is white bean bran extract (112.203 μmol/g; 117.243 μmol/g). Thus, all of the bran extracts have potential to be used in controlling blood glucose level for diabetic patient.